2012
DOI: 10.1152/ajpcell.00397.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between structure and kinetics of human SGLT1

Abstract: The Na(+)-glucose cotransporter hSGLT1 is a member of a class of membrane proteins that harness Na(+) electrochemical gradients to drive uphill solute transport. Although hSGLT1 belongs to one gene family (SLC5), recent structural studies of bacterial Na(+) cotransporters have shown that Na(+) transporters in different gene families have the same structural fold. We have constructed homology models of hSGLT1 in two conformations, the inward-facing occluded (based on vSGLT) and the outward open conformations (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
126
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(132 citation statements)
references
References 49 publications
(91 reference statements)
6
126
0
Order By: Relevance
“…S10), potentially allowing for a tighter seal in mammalian SGLTs. For hSGLT1, approximately two Na + ions are coupled to inward sugar transport, but we have found that mutation of the large hydrophobic side chains of the external gates to cysteine also increases the coupling ratio to as high as 6-1 for F453C (F424 in vSGLT) (29). This decreased coupling ratio suggests that mutations in the outer gate increase the probability that partially transported sugars return to the external solution.…”
Section: Resultsmentioning
confidence: 81%
“…S10), potentially allowing for a tighter seal in mammalian SGLTs. For hSGLT1, approximately two Na + ions are coupled to inward sugar transport, but we have found that mutation of the large hydrophobic side chains of the external gates to cysteine also increases the coupling ratio to as high as 6-1 for F453C (F424 in vSGLT) (29). This decreased coupling ratio suggests that mutations in the outer gate increase the probability that partially transported sugars return to the external solution.…”
Section: Resultsmentioning
confidence: 81%
“…The selection of mutants at putative Na1 and Na2 sites was guided by previous findings on the kinetics of hSGLT1 mutants (20,21) and the location of the Na1 and Na2 sites in LeuT (6). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although we speculate, based on our results, that the role of the conserved Na2 site is to stabilize substrate binding without conformational selection, analysis of other Na + -coupled transporters is needed to test this conjecture. Kinetic and conformational investigations of putative LeuT-fold members, hSGLT and PutP, have begun to tease out such details (23,36,37). Such analysis will also test a similarly tantalizing notion that subclasses of ion-coupled LeuT-fold transporters, defined by their transport modes and/or type and number of symported ions, share commonalities in their structural mechanics of alternating access.…”
Section: Discussionmentioning
confidence: 99%
“…simulations (20,21) and electron paramagnetic resonance (EPR) analysis (13,22) of LeuT demonstrated that Na + binding favors an outward-facing conformation although it is unclear which Na + site (or both) is responsible for triggering this conformational transition. Similarly, a role for Na + in conformational switching has been uncovered in putative human LeuT-fold transporters, including hSGLT (23). In Mhp1, the sole Na2 site has been shown to modulate substrate affinity (15); however, its proposed involvement in gating of the intracellular side (12, 21) lacks experimental validation.…”
mentioning
confidence: 99%